Chemical risk and chemical warfare agents: science and technology against humankind. Issue 9 (20th October 2016) - Guidotti, Matteo; Trifirò, Ferruccio
Abstract : After one century from the beginning of World War I, the threat of a possible usage of chemical warfare agents is back again. However, in our time, the potential targets of an attack with non-conventional toxic chemicals are civilian populations in a terrorist attack, rather than equipped and well-trained military troops in battlefields. Chemical weapons indeed are able to inflict not only material damages, but also noteworthy psychological consequences on the public opinion. An analysis of the most common misconceptions and a summary of the main advantages and disadvantages linked to the use of chemical weapons, in warfare actions or in terrorist attack, are discussed here.